Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.

Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, V. Hirekodathakallu (Phytochemistry, 2021)
Neem (Azadirachta indica L.) is well known for its medicinal, agricultural, and pesticidal applications since ages. The secondary metabolites, limonoids, confer these biological properties, wherein over 150 different limonoids have been reported from neem. To understand limonoid biosynthesis, we analyzed tissue-specific (kernel, pericarp, leaves, and flower) transcriptome that resulted in the identification of one farnesyl diphosphate synthase (AiFDS), one squalene synthase (AiSQS), three squalene epoxidases (AiSQE1, AiSQE2, and AiSQE3), two triterpene synthases (AiTTS1 and AiTTS2), cycloartenol synthase (AiCAS), two cytochrome P450 reductases, and ten cytochrome P450 systems. Comparative tissue-expression analysis indicated that AiFDS, AiSQS, AiSQE3, and AiTTS1 are expressed higher in the kernel than in the other tissues. Heterologously expressed recombinant AiTTS1 produced tirucalla-7,24-dien-3 beta-ol as the sole product. Expression profile data, phylogeny with triterpene synthases from Meliaceae and Rutaceae families, real-time PCR of different tissues, and transient transformation revealed the involvement of tirucalla-7,24-dien-3 beta-ol synthase (AiTTS1) in limonoid biosynthesis. Further, mutagenesis studies of AiTTS1 indicated that Y125 and F260 are probably involved in stabilization of dammarenyl cation. A 2.6-fold increase in production of tirucalla-7,24-dien-3 beta-ol was observed when AiSQE1 was coexpressed with mutant AiTTS1 in a yeast system. Furthermore, we functionally characterized the highly expressed cytochrome P450 reductases and cycloartenol synthase. This study helps in further analysis and identification of genes involved in limonoid biosynthesis in Meliaceae/Rutaceae and their production in a metabolically tractable heterologous system.
Keywords: 24-dien-3 beta-ol; Azadirachta indica A. Juss.; Cytochrome P450 system; Limonoids; Meliaceae; Tirucalla-7; Transcriptome

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis (vol 184, 112669, 2021) - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, Hirekodathakallu V. (Phytochemistry, 2021)

Targeted metabolite profiling and de novo transcriptome sequencing reveal the key terpene synthase genes in medicinally important plant, Couroupita guianensis Aubl - Thulasiram, Hirekodathakallu V.; Karegaonkar, Shrikant Jagannathrao; Sharma, Poojadevi; Kumar, Ashish; Ramkumar, Sudha; Pandreka, Avinash (Plant Genetic Resources-Characterization and Utilization, 2023)
The Lecythidaceae family tree, Couroupita guianensis Aubl, popularly known as Nagpushpa, is a widely cultivated ornamental tree with several uses in traditional medicine. The tree is revered as highly sacred in Indian traditional culture due to its uniquely shaped, fragrant flowers. Considering the significance, we were prompted to carry out the metabolite and transcriptome analysis of Nagapushpa. The flower, petals, stamen, stem and leaf of C. guianensis were metabolically profiled, and it was discovered that the flower tissue contained the highest terpenoid reservoir. A number of terpenoid pathway transcripts were also found in the flower tissue after transcriptome profiling. KEGG pathway mapping was carried out to correlate transcript sequences with the biosynthesis of different types of terpenes. We were able to clone three full-length terpene synthase gene candidates, i.e. monoterpene ocimene synthase, diterpene ent-kaurene synthase and sesquiterpene farnesene synthase. The transcript expression of selected terpene synthase genes was also verified in flower tissue. These cloned sequences were used for in silico structural investigations and protein function prediction at the level of 3D structure. The data presented in this study provide a comprehensive resource for the metabolic and transcriptomic profiles of C. guianensis. The study paves the way towards the elucidation of terpene biosynthetic pathway in C. guianensis and heterologous production of useful terpenoids in the future.
Keywords: Couroupita guianensis Aubl; flower; Metabolite profiling; terpene synthases; Transcriptomics